Search for Structurally Resembled Mn/Ca Cubane Core of the Oxygen Evolving Complex of Photosystem II Yielded MnIV, MnIII3MnII and MnIII2CaII2Entities: Structure and Magnetism. Issue 13 (12th April 2022) - Modak, Ritwik; Sikdar, Yeasin; Bhattacharya, Priyabrata; Kinyon, Jared S.; Dalal, Naresh; Bindra, Jasleen K.; Goswami, Sanchita
Abstract: The aim of the paper was to synthesize Mn/Ca entities that are structurally similar to the reported oxygen‐evolving complex (OEC) of photosystem II (PSII). Here we have ventured Schiff base combinations of racemic (±)‐3‐Aminopropane‐1, 2‐diol and Salicyladehyde (H3 L 1 )/ o ‐Vanillin (H3 L 2 ) with varied ratios of ligand : Ca II salt : Mn III salt. Interestingly, H3 L 2  : CaCl2  : MnCl2 (2 : 1 : 1) afforded [{Mn III 2 Ca II 2 (HL 2 )2 Cl2 (μ3 ‐OH)2 (H2 O)6 }Cl2  ⋅ 2H2 O] (3 ) whereas H3 L 1  : CaCl2  : Mn(acetate)2 (2 : 1 : 1) and H3 L 1  : CaCl2  : MnCl2 (2 : 1 : 2), generated [{Mn IV (HL 1 )2 }2  ⋅ 6H2 O](1 ) and [{Mn III 3 Mn II (HL 1 )3 (μ2 ‐Cl)3 (μ3 ‐O)} ⋅ 2CH3 OH ⋅ 2H2 O] (2 ) respectively. More importantly, we have been able to get a structure which offers partial similarity to reported structure of the OEC. Variable temperature magnetic susceptibility measurements have been performed in the 1.8–30 K region for all the compounds. Overall, these studies provide a critical understanding for the rational design and construction of synthetic OEC. Abstract : Experimental outcome for the synthesis of Mn/Ca complexes aiming the structural similarity to that of the Oxygen Evolving Complex (OEC) of Photosystem II (PS II) and the magnetic properties study. With the variation of ligand backbone and ratiometric reaction conditions result the formation of multinuclear homo‐ and heteronuclar complexes with interesting structural properties and partial structural similarity to the reported OEC.